Supporting national immunization technical advisory groups (NITAGs) in resource-constrained settings. New strategies and lessons learned from the Task Force for Global Health's Partnership for influenza vaccine introduction. Issue 28 (19th June 2019) - Ba-Nguz, Antoinette; Shah, Adeel; Bresee, Joseph S.; Lafond, Kathryn E.; Cavallaro, Kathy; Shefer, Abigail; Donadel, Morgane; Seward, Jane F.
Abstract: National Immunization Technical Advisory Groups (NITAGs) are multidisciplinary national experts who provide independent, evidence-informed vaccine policy recommendations to national health authorities. An essential NITAG function is to ensure that these decisions are grounded in the best available evidence generated through a systematic, transparent process. However, in many low- and middle-income countries (LMICs), experience with this decision making method is limited. The Task Force for Global Health manages the Partnership for Influenza Vaccine Introduction (PIVI) program in collaboration with the Centers for Disease Control and Prevention, Ministries of Health, corporate partners and others. During 2017, PIVI worked with its country partners and the World Health Organization regional and local offices to assess NITAG strengthening needs and to provide technical assistance in 7 LMIC countries (Laos Peoples Democratic Republic, Mongolia, Vietnam, Armenia, Côte d'Ivoire; Moldova and the Republic of Georgia). Our workshops supported general NITAG capacity building and the evidence-based review process using vaccines of interest to the country. For NITAGs reviewing evidence on seasonal influenza, we developed an influenza resource package to support their review and provide country-relevant information in an easy to use format. Of the seven NITAGs trained, six have applied some of the concepts learnt: revision or development of formal transparent, systematic procedures for their operations; preparation of recommendations on seasonal influenza vaccination using quality-assessed data from systematic searches and local data; and have applied the principles learned for making other new vaccine recommendations. Our experience confirms that LMIC NITAGs are considerably under-resourced without adequate technical support or access to global peer-reviewed literature. Ongoing support from NITAG partners must be secured and creative approaches might be needed to help countries achieve the GVAP 2020 target and support development of sustainable vaccine policies and programs.